La huaca Narihualá como medio de educación no formal - Aparicio Aldana, Zhenia Djanira (Mercurio Peruano, 2020)
The archaeological complex of Narihualá is regarded as one of the great architectural evidences in the valley of Piura, and hence its importance of study. Unfortunately it does not currently hold an adequate assessment of its relevance. Today the complex is mostly affected by climatic factors and also by human depredation. Because of this reason the research will focus on publicizing Huaca Narihualá as a means of nonformal education that promotes knowledge of Hispanic culture outside the classroom, according to necesary parameters and instruments for this purpose.